PELATIHAN WORSHIP LEADER UNTUK MENINGKATKAN KUALITAS PELAYANAN DI BETHANY CHURCH MALAYSIA KUCHING, MALAYSIA - Kathryn, Susanna; Burungan, Jummi; Chandra, Donny Charles; Wiryohadi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
Praise and worship have a reasonably large portion in worship. Therefore, praise and worship leaders must have proficiency in everything. Based on observations made by the Bethany Church Malaysia Kuching team, the problem was that the worship leader servants could still not provide worship leadership service. Therefore, this ecclesiastical Community Service aims to improve the quality of worship leader servants in carrying out their duties and responsibilities in ministry. The research method used is qualitative with data collection techniques: observation, interviews, and documentation. Meanwhile, the implementation method is through seminars, discussions, pastoral counseling, and performances such as talent search events. The result of this community service is that worship leader servants experience improvements in leadership skills, spirituality, and psychology. They are increasingly responsible for their duties as a servant worship leader.